2018
DOI: 10.4018/ijhcitp.2018100104
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethics in Developing Professionalism Within the Global ICT Community.

Abstract: This article investigates the development of Information Communication Technology (ICT) as a global profession with a specific focus on the role of ethics. It addresses three main issues: to what extent ethics contribute to the development of the professional identity of ICT practitioners; what practices and policies can promote the development of ICT ethics; how these practices and policies can usefully be coordinated internationally. Within the European policy framework, professional ethics is seen as one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Professional bodies continue to play a very important role in producing and disseminating ethical and standard guidelines for ICT professionals, for example the IEEE Ethically Aligned Design Guidelines provide guidance for ICT professionals (Shahriari and Shahriari, 2017). It should be noted that in contrast to other professions such as Medicine or Law, which have codes of ethics and possible penalties in place for noncompliance, the ICT profession still lacks of a coherent umbrella ethical framework (Thornley et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Professional bodies continue to play a very important role in producing and disseminating ethical and standard guidelines for ICT professionals, for example the IEEE Ethically Aligned Design Guidelines provide guidance for ICT professionals (Shahriari and Shahriari, 2017). It should be noted that in contrast to other professions such as Medicine or Law, which have codes of ethics and possible penalties in place for noncompliance, the ICT profession still lacks of a coherent umbrella ethical framework (Thornley et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the ICT field has a plethora of professional bodies, each with their own ethical guidelines, the voluntary nature of these organizations limits the effectiveness and reach of proposed standards and guidelines (Stahl et al, 2013). Not only does ethical noncompliance have no repercussions in ICT, there is also a lack of educational preparedness in ethical issues for aspiring professionals (Thornley et al, 2018).…”
Section: Responsible Innovationmentioning
confidence: 99%
“…The path is less clear than the other aspects of professionalism as people can disagree on ethical priorities and there are some cultural differences (Sherry, 2013). A recent review of ethics as part of ICT policy revealed both core agreements and differences within the EU, for example, former Eastern bloc countries held different perspectives than some Western European countries (Thornley et al, 2018).…”
Section: Ict Professionalismmentioning
confidence: 99%